2020
DOI: 10.1016/j.jaac.2020.08.411
|View full text |Cite
|
Sign up to set email alerts
|

51.1 a Qualitative Analysis: The Experience of Parents of Children With Autism Spectrum Disorder During the Covid-19 Pandemic

Abstract: Conclusions:The overall assessment of the safety plans was approximately 65%. The strengths of the safety plans include identifying support and coping skills. The safety plan template used on the inpatient unit does not include a line about means restriction, which automatically caused each plan to receive a zero in that category. We recommend that means restriction information be added to the discharge. Lower quality safety plans were more likely to have increased CPEP presentations/hospital readmissions. Saf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
7
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(17 citation statements)
references
References 0 publications
2
7
0
Order By: Relevance
“…For their affected children, parents reported changes in behaviour, poorer emotion regulation/management, and higher levels of anxiety, especially if routines were distorted, and compared to fewer [23] or less profound changes in the control group [6] . Further changes in behaviour included an increase in ASD core symptoms such as stereotypes [3] , but also an increase in aggression, hypersensitivity, sleep and appetite alterations [28] and decreased social skills [29] or fewer prosocial behaviours [6] .…”
Section: Figurementioning
confidence: 99%
See 1 more Smart Citation
“…For their affected children, parents reported changes in behaviour, poorer emotion regulation/management, and higher levels of anxiety, especially if routines were distorted, and compared to fewer [23] or less profound changes in the control group [6] . Further changes in behaviour included an increase in ASD core symptoms such as stereotypes [3] , but also an increase in aggression, hypersensitivity, sleep and appetite alterations [28] and decreased social skills [29] or fewer prosocial behaviours [6] .…”
Section: Figurementioning
confidence: 99%
“…Another line of advice also suggested structuring leisure time to some extent, e.g., by assigning different rooms for different activities, establishing rules for gaming and using the internet, or creating family playtimes [2,31] The difficulty of being at home all the time was indeed reported as the primary challenge by parents in the USA [26] . Implemented daily schedules, optimized for the child's needs, were reported as beneficial [29] . Parents had positive opinions on physical activities (e.g., health, social and psychological benefits), but barriers like having to work, security concerns, or insufficient online or tele-education (reported by parents as a lack in their own knowledge) made the implementation of physical activities difficult.…”
Section: Leisure Time Physical Activities and Internet And Social Media Usementioning
confidence: 99%
“…To date, quantitative studies have begun to illustrate the impact of the pandemic on the mental health and wellbeing of families with rare neurogenetic conditions but qualitative approaches are needed as they facilitate the opportunity to access the thoughts and feelings of individuals, and how these are used to understand their experiences. However, the majority of qualitative research exploring family mental health and wellbeing in the context of the pandemic has focused on the experiences of mothers, early phases of the pandemic (e.g., initial lockdown periods), and research in children with special educational needs and disability (SEND) or neurodevelopmental disorders (ND) has rarely specified the cause of SEND/ND (12,13,22,(14)(15)(16)(17)(18)(19)(20)(21).…”
Section: Introductionmentioning
confidence: 99%
“…Despite these limitations, in general, early qualitative findings suggest that children with SEND/ND experienced anxiety, low mood and social isolation, as well as difficulties understanding pandemicrelated changes that manifested in increased challenging behaviour (12,16,18,22). These studies have also underscored the many challenges faced by parents of children with SEND/ND.…”
Section: Introductionmentioning
confidence: 99%
“…Studies exploring the experiences of families of children on the autism spectrum during the COVID-19 pandemic suggest that many children showed an increased frequency of behavioural challenges, higher anxiety and poorer emotion regulation, and decreased social communication skills (Nonweiler et al, 2020 ; Parenteau et al, 2020 ). By using mixed methods, Oomen et al ( 2021 ) identified not only the burdens (e.g., loss of social contact, increased anxiety and stress) but also the benefits (e.g., reduced sensory and social overload) experienced by adults on the autism spectrum during the pandemic.…”
mentioning
confidence: 99%